The Rites of Knighthood : The Literature and Politics of Elizabethan Chivalry. - McCoy, Richard C. (Berkeley : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1989.
Intro -- Contents -- Illustrations -- Acknowledgments -- Introduction -- 1. Chivalric Compromise and Conflict -- 2. Robert Dudley: "Favour Sufficient" -- 3. Sir Philip Sidney: "The Shepherd Knight" -- 4. The Earl of Essex: "A Dangerous Image" -- 5. Samuel Daniel: "The Voyce of Present Times" -- 6. Edmund Spenser: "Furthest from... Present Time" -- Epilogue -- Notes -- Index
Description based upon print version of record.
JSTOR
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Chivalry in literature; Chivalry -- Great Britain -- History -- 16th century; Knights and knighthood in literature; Knights and knighthood -- Great Britain -- History -- 16th century; Politics and literature -- Great Britain -- History -- 16th century; Great Britain -- History -- Elizabeth, 1558-1603.; Poetics -- History -- 16th century; Chevalerie dans la littérature.; Chevalerie -- Grande-Bretagne -- Histoire -- 16e siècle.; Politique et littérature -- Grande-Bretagne -- Histoire -- 16e siècle.; Grande-Bretagne -- Histoire -- 1558-1603 (Élisabeth Ire); Poétique -- Histoire -- 16e siècle.; Chivalry; Chivalry in literature; English literature -- Early modern; Knights and knighthood; Knights and knighthood in literature; Poetics; Politics and literature; Great Britain; 1500-1700; Criticism, interpretation, etc; History